(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Amongst the many achievements of the first Chinese Civil Code, one of the most discussed is the provision of the so-called biorights. This paper focuses on articles 1006 to 1009, which mainly cover the new regulations on bioethics, biorights and new technologies, to show the breakthroughs made by the Chinese Civil Code. Despite the incomplete solutions provided for the referred norms and its blurred content, the code is a most welcome innovation in a country still seeking a bioregulation capable of handling its astonishing scientific achievements.